ANALYSIS OF THE EFFECT OF SERVICE QUALITY AND ORGANIZATIONAL CULTURE ON VILLAGE OFFICIAL PERFORMANCE AND COMMUNITY SATISFACTION: (A Study at Sanankulon Village Office, Sanankulon District, Blitar Regency) - Ferida Asih Wiludjeng; Risqa Latifatul Ulfa; Indria Guntarayana (JOSAR (Journal of Students Academic Research), 2020)
Village government as one of the government agencies that carry out public services must improve the quality of service in order to create satisfaction that can be felt by the community. However, there are still various arising issues in the community such as not meeting the people's expectations of the right to service that should be received by the community. Therefore, it is necessary to improve public services so that people's bad impression of the government can be fixed. The purpose of this study was to investigate and explain the implications of strategy and significant effect of service quality and organizational culture on the performance of village official and community satisfaction. This study adopted mixed method design. The results showed that service quality had a significant positive effect on village official performance; organizational culture had a significant positive effect on village official performance; service quality had a significant positive effect on community satisfaction; organizational culture had no significant effect on community satisfaction; village official performance had a significant positive effect on satisfaction community; and the implications of the strategy to improve village official performance and community satisfaction at Sanankulon Village Office were to include village officials in workshops to improve leadership competence and management of the village government, use finger print attendance continuously, create vision and mission, hold morning and end-of-the-day ceremonies, provide verbal and written warnings to undisciplined officials, and evaluate the criticisms and suggestions delivered by the community.